2002
DOI: 10.1203/00006450-200211000-00024
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation Inhibits Muscarinic Signaling in In Vivo Canine Colonic Circular Smooth Muscle Cells

Abstract: We investigated the effects of experimental colitis on the muscarinic signaling properties and contractile behavior of canine colonic circular smooth muscle. The hypotheses that inflammation 1) inhibits in vivo muscarinic receptor mediated contractions, and 2) alters receptor density or receptor-binding affinities were tested. Muscarine was infused close-intra-arterially in seven conscious dogs during normal and experimental colitis states. Colonic circular muscle contractions were recorded via surgically atta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 33 publications
0
19
1
Order By: Relevance
“…7 In this paper, the decreased contractile response to carbachol in IL-10 knockout mice with the reduced expression of M 2 receptor in the inflamed proximal colon is different from some other literature. 6,7 To clarify this difference, further study on M 3 receptor is necessary. Finally, concern can be raised about the electrical field stimulation (EFS) experiments reported in this article.…”
contrasting
confidence: 55%
See 3 more Smart Citations
“…7 In this paper, the decreased contractile response to carbachol in IL-10 knockout mice with the reduced expression of M 2 receptor in the inflamed proximal colon is different from some other literature. 6,7 To clarify this difference, further study on M 3 receptor is necessary. Finally, concern can be raised about the electrical field stimulation (EFS) experiments reported in this article.…”
contrasting
confidence: 55%
“…1,5 In addition, this study's investigation of the function and expression level of muscarinic type 2 (M 2 ) receptors is worthwhile in that the M 2 receptors may play a greater role in the inflamed colon. 6,7 These considerations make the article a strong one, and its conclusions can serve as a stepping stone to investigate several unanswered problems in gastrointestinal (GI) smooth muscle biology as follows. One such problem is the causality of the relationship between loss of c-KIT expression in specific ICC such as myenteric ICC (ICC-MY) or ICC associated with the submuscular plexus (ICC-SMP) and loss of spontaneous contraction in the proximal colon of mouse.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, Nazarov et al [29] reported that CRP, which increases during inflammatory states, may result in AA by capturing ACh or binding to the ACh receptor, whereas Tsuruta et al [30] reported that plasma AA was related to CRP in critically ill and injured patients. Furthermore, Horiuchi et al [31] reported that an endogenous immunologically active peptide (apelin) inhibited cholinergic activity by binding to the ACh receptor, and Jadcherla [32] found that inflammation inhibited muscarinic receptormediated signaling. Therefore, the downregulation of ACh in the central nervous system causes AA in both the central and peripheral systems by way of inflammation.…”
Section: Discussionmentioning
confidence: 99%